Concurrent training effect on muscle fibers in Wistar rats - Robson Chacon Castoldi; Regina Celi Trindade Camargo; Alan José Barbosa Magalhães; Guilherme Akio Tamura Ozaki; Fábio Yoshikazu Kodama; Sérgio Minoru Oikawa; Marcelo Papoti; José Carlos Silva Camargo Filho (Universidade Estadual Paulista (UNESP), 2013)
The aim of the present study was to determine the modeling of muscle fibers in rats submitted to different exercise protocols. Fifty-five Wistar rats were submitted divided into four different groups: Control group (CG; N=16); endurance training group (ETG; N=13), strength training group (STG; N=13) and concurrent training group (CTG; N=13). The intensity of endurance training was determined by the critical workload. Statistical analysis involved the Kruskal-Wallis test for multiple comparisons, followed by Dunn's post test (p<0.05). All animals submitted to training exhibited an increase in the cross-sectional area of the muscle fibers. The largest increase (p>0.05) occurred in the STG and CTG at both four (mean:2952,95 ± 878,39 mean:2988,84 ± 822,58) and eight weeks respectively (mean:3020,26 ± 800.91; mean:3104,91 ± 817,87). The findings demonstrate similar results obtained with strength training and concurrent training, with a greater increase in muscle fiber area in both groups in comparison to the control group and group submitted to endurance training.